Porównanie ciągłych i etapowych modeli oceny i doskonalenia procesów programowych - Kobyliński, Andrzej; Chodoła, Tomasz (The Comparison of Continuous and Staged Models for Software Process Assessment and Improvement, 2005)
The paper provides a short overview of models and standards of software process assessment and improvement (SPA/SPI). All the models can be grouped into two classes: staged and continuous. Staged architecture models assess software organization capability and explicitly describe it in terms of maturity level. Continuous architecture models evaluate individual processes' capability, not organization as a whole. Advantages and disadvantages for both representations (architectures) are described.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 288-295